Starvation therapy enabled "switch-on" NIR-II photothermal nanoagent for synergistic in situ photothermal immunotherapy. (June 2022) - Pu, Yinying; Wu, Wencheng; Zhou, Bangguo; Xiang, Huijing; Yu, Jifeng; Yin, Haohao; Zhang, Yan; Du, Dou; Chen, Yu; Xu, Huixiong
Abstract: Tumor photonic hyperthermia in the second near-infrared biowindow (NIR-II) represents the distinct therapeutic modality owing to the high tissue penetration and excellent spatiotemporal controllability. However, the non-specific "always on" nature of conventional NIR-II photothermal agents and the photothermal therapy (PTT)-associated tumor metastasis have restricted the progress of photonic hyperthermia. In this study, a cascade nanoreactor (denoted as LGT) based on clinically transformable liposomal nanoparticles is rationally engineered by encapsulating a pro-photothermal agent, 3, 3′, 5, 5′-tetramethylbenzidine (TMB), and a tumor starvation mediator, glucose oxidase (GOD), for starvation therapy activated in-situ photothermal immunotherapy in inhibiting primary and metastasized tumors. Accompany with GOD-mediated intratumoral glucose depletion and hydrogen peroxide generation, the pro-photothermal agent is in-situ converted into the NIR-II absorbing charge transfer complex (CTC) in tumor microenvironment (TME). Collaboratively, glucose deprivation not only cuts the energy supply to tumor cells but also makes LGT sensitive to photothermal ablation. Upon NIR-II laser irradiation, LGT-mediated in-situ PTT ablates primary tumors, and further elicits the exposure of tumor-associated antigens. Importantly, the combination of starvation therapy enabled in situ PTT with anti-CTLA-4 checkpoint blockade therapy effectively inhibits distant tumor growth and tumor metastasis. Therefore, the present work provides a representative paradigm for tumor starvation therapy activated "switch-on" photothermal immunotherapy of cancer. Graphical Abstract: ga1 Highlights: A cascade nanoreactor has been rationally designed for starvation therapy-activated in-situ photothermal immunotherapy. Achieving starvation therapy-enabled in situ photothermal immunotherapy. In-depth mechanistic clarification of starvation therapy-enabled in situ photothermal immunotherapy by RNA sequencing.